(untitled) (Revista de Ciências Agroveterinárias, 2024)
Beans are an important constituent of the Brazilian diet, and the search for cultivars with good culinary characteristics and adapted to the place of cultivation is necessary. It is known that there is a wide genetic diversity for common bean landrace cultivars. Still, little is known experimentally about the behavior of these cultivars when produced under organic cultivation. This work aimed to evaluate the technological quality of common bean landraces produced under organic cropping system. Twenty-six cultivars were used, four commercial and twenty-two landraces, originating from the Active Bean Germplasm Bank (BAF) of Santa Catarina State University – Agroveterinary Sciences Center (UDESC/CAV), produced in organic and conventional cultivation, in two crops. Cooking time and resistance, percentage of water absorption and broken grains and total soluble solids were evaluated. The shortest cooking time for the grains cultivated in the organic system (18 to 22 minutes) was obtained. The cultivars that had a percentage of unbroken grains between 60 and 80% showed a higher content of total soluble solids in the broth. Based on the genetic diversity for technological quality in organic cropping system, the use of cultivars, BAFs: 60, 23, 81, 13, 68, 55, 75 and 36 are indicated to integrate genetic improvement programs or to be used by small farmers for bean production.